A highly sensitive fluorimetric method for determination of lenalidomide in its bulk form and capsules via derivatization with fluorescamine - Darwish, Ibrahim A (BioMed Central, 2012)
BACKGROUND: Lenalidomide (LND) is a potent novel thalidomide analog which demonstrated remarkable clinical activity in treatment of multiple myeloma disease via a multiple-pathways mechanism. The strong evidences-based clinical success of LND in patients has led to its recent approval by US-FDA under the trade name of Revlimid® capsules by Celgene Corporation. Fluorimetry is a convenient technique for pharmaceutical quality control, however there was a fluorimetric method for determination of LND in its bulk and capsules. RESULTS: A novel highly sensitive and simple fluorimetric method has been developed and validated for the determination of lenalidmide (LND) in its bulk and dosage forms (capsules). The method was based on nucleophilic substitution reaction of LND with fluorescamine (FLC) in aqueous medium to form a highly fluorescent derivative that was measured at 494 nm after excitation at 381 nm. The factors affecting the reaction were carefully studied and optimized. The kinetics of the reaction was investigated, and the reaction mechanism was postulated. Under the optimized conditions, linear relationship with good correlation coefficient (0.9999) was found between the fluorescence intensity and LND concentration in the range of 25–300 ng/mL. The limits of detection and quantitation for the method were 2.9 and 8.7 ng/mL, respectively. The precision of the method was satisfactory; the values of relative standard deviations did not exceed 1.4%. The proposed method was successfully applied to the determination of LND in its bulk form and pharmaceutical capsules with good accuracy; the recovery values were 97.8–101.4 ± 1.08–2.75%. CONCLUSIONS: The proposed method is selective and involved simple procedures. In conclusion, the method is practical and valuable for routine application in quality control laboratories for determination of LND.